Factors influencing usage of e-wallet among Uum students - Liu, Yanran (2019)
The objective of this paper is to study the factors that affect the usage of E-wallet. Based on the technology acceptance model, the effects of perceived ease of use, perceived usefulness, social influence, security and convenience on the use of E-wallet are analyzed. In this study, 400 questionnaires were distributed to UUM students and 372 valid questionnaires were collected. SmartPLS is used to analysed the hypothesis whilst SPSS is used to analyse the descriptive data. The results show that perceived usefulness, perceived ease of use, security and convenience are significantly related to the behavior intention to use E-wallet, and social impact is not significantly related to the usage of E-wallet. This paper also discusses the limitations of this study, and puts forward suggestions for future research, providing better ideas for future researchers and E-wallet operators, and further popularizing the use of E-wallet.